146k views
4 votes
Which constants could each equation be multiplied by to eliminate the x-variable using addition in this system of equations? 2 x + 3 y = 25. Negative 3 x + 4 y = 22.

1.The first equation can be multiplied by –3 and the second equation by 2.
2. The first equation can be multiplied by –4 and the second equation by 2.
3. The first equation can be multiplied by 3 and the second equation by 2.
4. The first equation can be multiplied by 4 and the second equation by –3.

1 Answer

4 votes

Answer:

3. The first equation can be multiplied by 3 and the second equation by 2.

Explanation:

2 x + 3 y = 25 (1)

-3 x + 4 y = 22 (2)

Multiply equation (1) by 3 and (2) by 2.

3(2x) = 6x

2(-3x) = -6x

When you add the two equations, x will get cancelled last

User Kolhapuri
by
5.3k points